Morphologic alterations resulting from denervation of the diaphragm in rats - Torrejais, M. M.; Soares, J. C. [UNESP]; Matheus, S. M. M. [UNESP]; Francia-Farje, L. A. D. [UNESP]; Mello, J. M.; Vicente, E. J. D. (Soc Chilena Anatomia, 2012)
The morphological alterations that occur in the muscle fibers of denervated rat diaphragms were studied. Fifteen adult male albino rats (Rattus norvegicus) with a mean weight of 200 g and about 60 days of age were used. Chronically denervated diaphragms were obtained and the animals were sacrificed after 4, 8 and 12 weeks of denervation. The left antimere of the diaphragm was denervated by sectioning of the phrenic nerve and the right antimere served as control. Each antimere was divided into two fragments, which were used for histological (RE.) and histoenzymological (NADH-TR and myofibrillar ATPase). After 4 weeks, denervated muscle fibers showed important light microscopic alterations: atrophy with angular profiles in cross-sections, cytoplasm containing vacuoles, enlarged interstitial space with increased connective tissue, cellular infiltration, and muscle fibers without defined contours. The most marked alterations being observed for type IIb and ha fibers. Eight and 12 weeks after denervation, the NADH-TR reaction showed that it was impossible to characterize the muscle fibers based on their metabolic profile.

Fueron estudiadas las alteraciones morfológicas de las fibras musculares del diafragma denervado de ratas. Se utilizaron 15 ratas albinas (Rattus norvegicus) machos, adultos, con peso promedio de 200g y cerca de 60 días de edad. Se denervó el diafragma y después de 4, 8 y 12 semanas los animales fueron sacrificados. El antímero izquierdo del diafragma fue denervado por sección del nervio frénico y el antímero derecho fue utilizado como control. Cada antímero fue dividido en fragmentos, utilizados para el estudio histológico (H-E), histoenzimológico (NADH-TR y ATPasa miofibrilar). Después de 4 semanas las fibras musculares denervadas presentaron alteraciones importantes en lamicroscopía de luz: atrofia con perfiles angulados en secciones transversales; citoplasma con vacuolas; aumento del espacio intersticial con aumento de tejido conjuntivo; infiltración celular y fibras musculares sin contornos definidos, siendo las alteraciones más marcadas en las fibras tipo IIb e IIa. Después de 8 y 12 semanas de denervación la reacción para NADH-TR demuestra que es imposible caracterizar a las fibras musculares a través de su perfil metabólico.
Alteraciones morfológicas resultantes de la denervación del diafragma en ratas
Keywords: Diaphragm; Muscle fiber; Denervation; Rat